2019
DOI: 10.1155/2019/6160927
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Associated Factors of Depression among Patients with Diabetes at Jazan Province, Saudi Arabia: A Cross-Sectional Study

Abstract: Context Patients with diabetes mellitus (DM) have a poorer quality of life when compared with patients without DM. In fact, one in every five diabetic patients suffers from comorbid depression, which can lead to poor management, poor compliance with treatment, and low quality of life. Therefore, we assessed the prevalence of depression and identified its associated factors among diabetic patients at Jazan Province, KSA. Methods and Materials A cross-sectional study was conducted among 500 diabetic patients att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
16
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 28 publications
6
16
1
Order By: Relevance
“…Moreover, lower education level was reported to be a risk factor for depression and stress in our study. Similar findings were reported in patients with CHB (Vu et al., 2019) and diabetes (Madkhali et al., 2019). It could be attributed to the fact that more educated patients can have better access to information about their health conditions and be more aware and understand the treatment plan.…”
Section: Discussionsupporting
confidence: 87%
“…Moreover, lower education level was reported to be a risk factor for depression and stress in our study. Similar findings were reported in patients with CHB (Vu et al., 2019) and diabetes (Madkhali et al., 2019). It could be attributed to the fact that more educated patients can have better access to information about their health conditions and be more aware and understand the treatment plan.…”
Section: Discussionsupporting
confidence: 87%
“…The prevalence of this study was relatively higher than the studies reported from Saudi Arabia, Iran, India, United Kingdome, Northeast Brazil, South Brazil, Uganda and Nigeria hospitalized patients were 25.5%, 34.8%, 44.1%, 8.1%, 27.1%, 33.7%, 22.5% and 22% respectively (22-29) and similarly higher than the studies reported from Vietnam, Jazan Province of Saudi Arabia, Southern Taiwan, Hawassa, Ethiopia, Amanuel mental health hospital, Ethiopia, Menlike II hospital, Ethiopia were 5.4%, 20.6%,38%, 22.1%, 27.1% and 23.2% respectively (5,(30)(31)(32)(33)(34). This variation might be resulted from change in methodological difference, study population; which were data taken from chronic medical surgical and trauma inpatients including intensive care unit inpatients, difference in screening and diagnostic questionnaire tool used; some researchers used like Kessler scale, Burden Assessment Scale, Hospital Depression, Anxiety and Stress Scale to measure mental distress and other sociodemographic and environmental factors may increase the prevalence of mental distress on this study.…”
Section: Discussionmentioning
confidence: 68%
“…Regional State hospitals of Ethiopia respectively (13,17,22,24,30,32,34). This outcome might be resulted from inpatients with two or more chronic comorbid disorder might have different physical illness and the self-reporting questionnaire diagnostic tool also included some symptoms of physical illness and patients with comorbid disorder were limited from their daily physical activities; which might result to high report of mental distress (11).…”
Section: Discussionmentioning
confidence: 99%
“…Lower education level was another significantly associated factor with MHD in this study. Many other studies have reported a similar association of lower educational status with MHD in the diabetes population as well as in the general population[37–40]. Lower education level diabetics have limitations in coping[41] to deal with diabetes complications and other comorbidities as well as their general psychosocial problems.…”
Section: Discussionmentioning
confidence: 79%
“…Most of the elderly diabetics in this study population were living in an urban area (63.8%); however, the proportion of MHD among elderly diabetics more likely occur in rural areas. Previous studies showed different conclusions regarding the higher prevalence of MHD in rural or urban areas[25, 40, 43], while other studies reported separately[11, 38, 44]. In developed countries, MHD tends to be higher in urban residents[45].…”
Section: Discussionmentioning
confidence: 99%